DEVELOPING E-LEARNING BASED ENGLISH MATERIALS WITH THE INSERTION OF BALINESE CULTURE FOR THE TENTH GRADE STUDENTS OF TOUR AND TRAVEL DEPARTMENT AT SMKN 1 SINGARAJA - ., I Gede Oka Yasa Aryawan; ., Prof. Dr. Putu Kerti Nitiasih, M.A.; ., Putu Eka Dambayana S., S.Pd., M.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2017)
Penelitian ini merupakan penelitian dan pengembangan (R&D) yang bertujuan untuk: (1) mengidentifikasi jenis materi Bahasa Inggris yang diperlukan untuk siswa kelas 10 jurusan Unit Perjalanan Wisata (UPW) di SMK N 1 Singaraja; (2) mengidentifikasi desain materi Bahasa Inggris Inggris yang diperlukan untuk siswa; (3) mengukur kualitas produk e-learning untuk siswa Jurusan UPW; (4) mengidentifikasi respon guru dan murid terhadap produk yang dikembangkan. Penelitian ini dilakukan berdasarkan pada desain penelitian dan pengembangan oleh Lee & Owen (2004). Data penelitian dikumpulkan melalui wawancara, observasi, dokumen, angket, uji ahli dan uji lapangan. Data dianalysis menggunakan metode analisis deskriptif kualitatif, model analisis data interaktif, dan Inter-rater Agreement Model. Hasil penelitian menunjukkan bahwa (1) siswa membutuhkan materi Bahasa Inggris yang sesuai dengan jurusannya dan pekerjaan mereka; (2) desain materi dikembangkan berdasarkan kebutuhan siswa; (3) materi Bahasa Inggris dengan tambahan budaya Bali berbasis e-learning untuk siswa jurusan UPW dikategorikan sebagai materi berkualitas tinggi; dan (4) perspektif guru dan murid terhadapa produk menunjukan respon yang positifKata Kunci : R & D, e-learning, ESP, Tour and Travel, Balinese Local Culture This study was a Research and Development (R&D) study which aimed at: (1) identifying kinds of English materials needed for the tenth grade students majoring in Tour and Travel at SMK N 1 Singaraja; (2) identifying the design of English materials needed by the students (3) measuring the quality of the E-learning English materials; (4) identifying students’ and teachers’ response toward the implementation of the developed e-learning materials. This study was conducted based on the research and development design proposed by Lee and Owens (2004). The data of the research were collected from an interview, observation, document analysis, questionnaire, expert judgments, and field test. The data were analyzed by using descriptive qualitative analysis, Interactive data analysis model, and inter-rater agreement model. The study showed that (1) the students need English materials that were appropriate to their major and with their career in the future; (2) the design of the materials was developed based on the students’ needs; (3) the e-learning based English materials with the insertion of Balinese local culture for students of Tour and Travel Department were categorized as highly qualified; and 4) teachers’ and students’ perspectives toward the product showed positive response.keyword : R & D, e-learning, ESP, Tour and Travel, Balinese Local Culture